2015
DOI: 10.1093/icvts/ivv159
|View full text |Cite
|
Sign up to set email alerts
|

Management of visceral malperfusion complicated with acute type A aortic dissection

Abstract: We believe that if visceral ischaemia is severe and extensive in patients with type A aortic dissection, abdominal surgery should proceed before the aorta is surgically approached to avoid further irreversible ischaemic damage caused by circulatory arrest in organs with compromised perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…In the setting of visceral malperfusion, the correct management and timing of aortic repair is still a subject of debate. While there is general agreement that early reperfusion is critical for mesenteric malperfusion, it is not clear whether initial central aortic repair or percutaneous and/or extra-anatomic reperfusion best accomplishes that end (3,30,31). Some groups, given the unpredictable nature of TAAD and its potential for rupture, suggest immediate central aortic repair followed by investigation and treatment of residual malperfusion (3,32).…”
Section: Mesenteric Malperfusionmentioning
confidence: 99%
“…In the setting of visceral malperfusion, the correct management and timing of aortic repair is still a subject of debate. While there is general agreement that early reperfusion is critical for mesenteric malperfusion, it is not clear whether initial central aortic repair or percutaneous and/or extra-anatomic reperfusion best accomplishes that end (3,30,31). Some groups, given the unpredictable nature of TAAD and its potential for rupture, suggest immediate central aortic repair followed by investigation and treatment of residual malperfusion (3,32).…”
Section: Mesenteric Malperfusionmentioning
confidence: 99%
“…This delayed treatment strategy involved early endovascular treatment with a complete or partial resolution of organ ischemia, followed by timely aortic surgeries. [16,17] While this management approach may be beneficial in a specific subpopulation, [18,19] Given the high mortality of patients with mesenteric malperfusion (40-100%), initial management with an interventional procedure treating the condition should be considered. [20,21] In fact, previous data suggested that mesenteric malperfusion was associated with the highest mortality rates when compared to malperfusions occurring in any other organ systems.…”
Section: [9]mentioning
confidence: 99%
“…However, few studies have examined CPB improvement strategies aimed at visceral and lower-body perfusion. We and others propose that maintaining the continuity of lower-body blood flow may be important for avoiding visceral organ dysfunction and post-operative mortality [42,43].…”
Section: Discussionmentioning
confidence: 99%